Hubungan antara peran keluarga dengan tingkat depresi pada lansia umur 45-59 tahun di posyandu lansia puskesmas dinoyo kecamatan lowokwaru kota malang - Yani; Susilaningsih; Yeni Fitria (PROFESSIONAL HEALTH JOURNAL, 2022)
Hypertension is the beginning of various diseases that claimed the lives of so many people. Malignant disease commonly called the nickname "silent killer" which makes the patient trapped in the perception that he was in good health - just fine. High sodium intake is one of the main causes of primary hypertension, and family support is an alternative way of preventing sodium intake. This study aims to determine the relationship between family support for intake of sodium primary hypertension patients aged 45-59 years old. The research design used is descriptive correlative through cross sectional approach with the number of samples as many as 30 people in Puskesmas Dinoyo with sampling technique in total sampling. The data of the research were analyzed using spearman correlation and got the result of the respondents with the support of the family was in the category of less equal to 63,3% and sodium intake was in high category equal to 53,3%, result of analysis with correlation coefficient value equal to -0,534 with significance value equal to 0,002 which means the value of p <0.01 and Ha accepted that indicates a relationship between family support for sodium intake of hypertensive patients aged 45-59 years old at Puskesmas Dinoyo. The value of correlation coefficient of -0.534 which means the nature of the relationship is inversely proportional, the better the family support the lower the sodium intake. It is hoped that family members will give their maximum support to family members suffering from primary hypertension in terms of sodium intake.